Structural Determinants of the Gain-of-Function Phenotype of Human Leukemia-associated Mutant CBL Oncogene - Nadeau, Scott A. (J Biol Chem, 2017)
Mutations of the tyrosine kinase-directed ubiquitin ligase CBL cause myeloid leukemias, but the molecular determinants of the dominant leukemogenic activity of mutant CBL oncogenes are unclear. Here, we first define a gain-of-function attribute of the most common leukemia-associated CBL mutant, Y371H, by demonstrating its ability to increase proliferation of hematopoietic stem/progenitor cells (HSPCs) derived from CBL-null and CBL/CBL-B-null mice. Next, we express second-site point/deletion mutants of CBL-Y371H in CBL/CBL-B-null HSPCs or the cytokine-dependent human leukemic cell line TF-1 to show that individual or combined Tyr → Phe mutations of established phosphotyrosine residues (Tyr-700, Tyr-731, and Tyr-774) had little impact on the activity of the CBL-Y371H mutant in HSPCs, and the triple Tyr → Phe mutant was only modestly impaired in TF-1 cells. In contrast, intact tyrosine kinase-binding (TKB) domain and proline-rich region (PRR) were critical in both cell models. PRR deletion reduced the stem cell factor (SCF)-induced hyper-phosphorylation of the CBL-Y371H mutant and the c-KIT receptor and eliminated the sustained p-ERK1/2 and p-AKT induction by SCF. GST fusion protein pulldowns followed by phospho-specific antibody array analysis identified distinct CBL TKB domains or PRR-binding proteins that are phosphorylated in CBL-Y371H-expressing TF-1 cells. Our results support a model of mutant CBL gain-of-function in which mutant CBL proteins effectively compete with the remaining wild type CBL-B and juxtapose TKB domain-associated PTKs with PRR-associated signaling proteins to hyper-activate signaling downstream of hematopoietic growth factor receptors. Elucidation of mutant CBL domains required for leukemogenesis should facilitate targeted therapy approaches for patients with mutant CBL-driven leukemias.